The support of internal communication during organizational change processes - Abrantes, A. C. M.; Bakenhus, M.; Ferreira, A. I. (Journal of Organizational Change Management, 2024)
Purpose The literature on communication in change processes, although fundamental, appears to still be very fragmented. The purpose of this study is to provide an explanatory and integrated framework for the communication process in organizational change processes. Design/methodology/approach The authors conducted 22 semi-structured interviews with employees from 21 companies and 13 different sectors in Germany. The four-step Gioia inductive coding approach was adopted as the methodological approach of the current study. Findings A final research model reveals that the organizational change communication (OCC) process is marked by specific change-restraining forces associated with the fear of the unknown, habits and convenience. Results also suggest the importance of communication timing and factors that help shape the OCC process, namely the scope, contents and channels of the communication process. Finally, the current research highlights contextual variables of the OCC process, such as credibility or the level of honesty. Originality/value The importance of OCC, in particular the understanding of the scope, contents of the message and the channels of communication adopted in the change management process, are important variables in the complexity of change. The paper illustrates the intricacy of communication in change and reinforces the internal and external variables that help shape the OCC process, with implications for change agents and scholars.